EPISTEMOLOGI PENDIDIKAN ANARKISTIK PERSPEKTIF MIKHAIL BAKUNIN DAN IMPLIKASINYA DALAM KURIKULUM MERDEKA DI INDONESIA - Faishol, Riza; Anugrah, Dendy Wahyu (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Implementing an independent curriculum not only requires contextual application, but also has challenges and obstacles that cannot be forgotten. Education in Indonesia, with its existing socio-culture, finds a very clear culmination point, namely how educators and students can understand the objectives of the curriculum itself. Just forming an education system that is able to adapt to the globalization that is occurring does not have a significant impact on education. So, concrete steps are needed to realize the goals of an independent curriculum which seeks to develop the potential and competence of students as well as the skills of educators as facilitators. So, research is needed that seeks to provide a view that is in line with the goals of the independent curriculum, one of which is research that discusses anarchistic education from Mikhail Bakunin's perspective. Apart from helping in implementing and realizing the goals of the independent curriculum, this research also complements the perspective of education in Indonesia. The method used is a literature review to understand the definition and principles of anarchistic education. The research results show explicitly that Mikhail Bakunin's views on education have implications for the independent curriculum. The principles of anarchistic education can help in realizing the goals of the independent curriculum currently implemented in Indonesia.